2019
DOI: 10.1007/s41062-019-0227-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of soil structure interaction by the spectral element method

Abstract: This paper describes the dynamic analysis of soil-structure interaction by using the spectral element method (SEM). This numerical method is a powerful numerical technique suited for the dynamic tasks. In this case, numerical methods with highly developed computer technique become very efficient to analyze complex problems. The partial differential equation governing the motion is derived and solved by using SEM. Thus, the corresponding solutions are the eigenvalues of the problem, so natural frequencies are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…SEM was one of the powerful numerical techniques used for dynamic tasks. Boudaa and et al used SEM to study vibration of beams on non-classical support [12]. Monsalve et al estimated earthquake-induced direct losses using the performance assessment calculation tool in tall buildings and recommends including SSI effects to avoid underestimation [13].…”
Section: Introductionmentioning
confidence: 99%
“…SEM was one of the powerful numerical techniques used for dynamic tasks. Boudaa and et al used SEM to study vibration of beams on non-classical support [12]. Monsalve et al estimated earthquake-induced direct losses using the performance assessment calculation tool in tall buildings and recommends including SSI effects to avoid underestimation [13].…”
Section: Introductionmentioning
confidence: 99%
“…It reduces finite elements, degree of freedom, time, and space for computation. Boudaa, S. et al [20] validated the SEM method to differential transform method and analytical method and concluded that it converges fast than FEM and the soil property affects the mode shapes of vibration.…”
Section: Spectral Element Methods (Sem)mentioning
confidence: 99%
“…In the literature, the resistance or "draft force problem" has been tackled either experimentally, or by developing analytical models and using numerical methods [51]. Methods used for parameter estimation in different tool-soil interaction models have included multilayer neural networks and swarm intelligence [52], discrete element modeling [53], the finite element [50], and the spectral element method [54].…”
Section: Tool-soil Interactionmentioning
confidence: 99%